The government of beans : regulating life in the age of monocrops - Hetherington, Kregg (Duke University Press, 2020)
"THE GOVERNMENT OF BEANS is a multispecies ethnography on the proliferation of the vast soybean monocrop in Paraguay and its ensuing effects on the government, agriculture, population, and environment. As Kregg Hetherington shows, soy monocropping, which was expanding at an average of 200,000 square hectares per year at the turn of the twenty-first century, has consumed most of Paraguay's arable land, contributing to rising inequity, poor health, deforestation, and climate change. The book highlights the failed attempts by campesinos, NGOs, and the government to contain the soy monocrops. Hetherington largely focuses on a group of activist bureaucrats, which he refers to as the Government of Beans, who from 2008-2012 tested the hypothesis that a stronger state, empowered to intervene in the excesses of the soy industry, would be able to slow down the advance of agribusiness interests, and thereby help to promote rural welfare and environmental health. These activist bureaucrats failed in their attempts, and Hetherington shows that what happened in Paraguay has profound global significance. The book is divided into three parts. Part I: A Cast of Characters presents backstories of the critical actors-- including individuals, plants, government agencies, and political coalitions-- that made up the Government of Beans. This section explores the challenges in defining an adequate temporality for regulation, since the growth of the monocrop was in itself very unpredictable. Part II: The Government of Beans tells the story of how the Government of Beans attempted and failed to change the way the Paraguayan state regulated its agricultural sector and the tensions that ensued in the process. More specifically, the regulations implemented by the Government of Beans failed to predict certain outcomes, such as how they would be individually implemented by farmers as well as the rapidity and effects of the growing soy, which seemed to have a life of its own. The actions of the Government of Beans were thus always experimental in nature, hoping for better outcomes and a better future with no guarantee about the effects. Part III: The Long Green Revolution offers a genealogical look at the way the intensification of agriculture has always implicated state actors. Developing a theory of "agribiopolitics," this section calls for a better understanding about the intimate, but rarely theorized, political relationship between human health and plant health, and a reflection on why welfare policies and ecological modernism are insufficient frames to work our way out of environmental destruction. This book will be of interest to students and scholars in anthropology, geography, Latin American studies, and environmental studies"--